Protagonistas de sua história: territorialidades femininas da comunidade quilombola Dona Juscelina em Muricilândia-TO - Sousa, Elaine da Silva (Universidade Federal do Tocantins, 2021)
The Quilombola Community Dona Juscelina, which is located in the city of Muricilândia-TO, has always had women actively present in the activities and decisions in and of the community, with Dona Juscelina as a woman and matriarch of the community. Other women from the quilombo found in Dona Juscelina an incentive to put themselves in leadership roles and fight against the invisible barriers of society. Thus, this research has as study the female protagonists of the Quilombola Community Dona Juscelina, located on the margins of the TO - 222 highway that is in the northern region of the country as well as in the urban perimeter of the city of Muricilândia-TO. The general objective was to understand the process of identity construction and the territorialities of the female protagonists in the Quilombola Community Dona Juscelina in Muricilândia-TO, and as specific objectives: to identify the female protagonists of the Quilombola Community Dona Juscelina; to know the territorialities and identities built by the female protagonists in Quilombo Dona Juscelina; reflect on the process of building the identity of quilombola women and their territorialities; and to characterize and specialize the activities of the female protagonists of Quilombo Dona Juscelina. To comply with the proposed objectives, a qualitative methodology was used, with the following procedures: bibliographic research (books, magazines, periodicals, theses and dissertations), participant observation, oral history, personal testimonies with audio recordings in authorized individual interviews by the protagonists, from the use of digital resources and platforms (Google Meet) respecting the rules of distance due to the pandemic of COVID-19. The theoretical framework used sought to dialogue with three elements that are key in the dissertation: territoriality, female protagonism and quilombola community. The analyses carried out show that the identities of the protagonists of Quilombo Dona Juscelina are in constant construction and reconstruction, their territorialities are present in every action performed inside and outside their community and, yet, they struggle daily for their ancestral territory and against internal barriers. visible from the patriarchy.